Experiences of African American Breast Cancer Survivors Using Digital Scales and Activity Trackers in a Weight Gain Prevention Intervention: Qualitative Study - Power, Julianne M; Tate, Deborah F; Valle, Carmina G (JMIR Publications, 2020)
BackgroundThe use of digital tools to promote daily self-weighing and daily activity tracking may be a promising strategy for weight control among African American breast cancer survivors (AABCS). There have been no studies exploring the acceptability and feasibility of using digital tools for weight control or qualitative studies characterizing perceptions of daily self-weighing and daily activity tracking among AABCS. ObjectiveThis study aimed to explore the subjective experiences of daily self-weighing and daily activity tracking using digital tools, including wireless scales and activity trackers, in a sample of AABCS participating in two technology-based weight gain prevention interventions over 6 months. MethodsSemistructured interviews (N=21) were conducted in person or over the phone, were audio recorded, and then transcribed verbatim. Each transcript was read to identify key themes and develop a codebook. Each transcript was coded using Atlas.ti software, and code outputs were used to identify overarching themes and patterns in the data. ResultsOn average, participants were 52.6 (SD 8.3) years of age, with obesity at baseline (BMI 33.1 kg/m2, SD 5.9), and weighed on 123.4 (SD 48.0) days out of the 168 days (73.5%) in the study period. Women tended to attribute their weight gain to cancer treatment and framed program benefits in terms of improved quality of life and perceptions of prolonging their survival following treatment. Using the smart scale for daily self-weighing was viewed as the tool by which participants could control their weight and improve their health and well-being posttreatment. The activity tracker increased awareness of physical activity and motivated participants to be more active. ConclusionsParticipants reported positive experiences and benefits from daily self-weighing and daily activity tracking. Findings suggest that daily self-weighing and daily activity tracking using digital tools are well-received, acceptable, and feasible intervention strategies for AABCS in the context of posttreatment weight management.